Gender Differences in Carbohydrate Metabolism and Carbohydrate Loading - Willoughby Darryn; Wismann Jennifer (Taylor & Francis Group, 2006)
Abstract Prior to endurance competition, many endurance athletes participate in a carbohydrate loading regimen in order to help delay the onset of fatigue. The "classic" regimen generally includes an intense glycogen depleting training period of approximately two days followed by a glycogen loading period for 3-4 days, ingesting approximately 60-70% of total energy intake as carbohydrates, while the newer method does not consist of an intense glycogen depletion protocol. However, recent evidence has indicated that glycogen loading does not occur in the same manner for males and females, thus affecting performance. The scope of this literature review will include a brief description of the role of estradiol in relation to metabolism and gender differences seen in carbohydrate metabolism and loading.